Perceived value in peer-to-peer (P2P) accommodation: A case of Airbnb / Izyanti Awang Razli, Salamiah A. Jamal and Mohd Salehuddin Mohd Zahari - Awang Razli, Izyanti; A. Jamal, Salamiah; Mohd Zahari, Mohd Salehuddin (UiTM Press, 2017)
Airbnb is a trusted community marketplace for people to list, discover, and book unique accommodations around the world. This online platform which is also known as Peer-to-Peer (P2P) accommodations functioned through which ordinary people rent out their spaces as accommodation for tourists. This new and evolving sector of access-based hospitality service poses few questions for the future direction of the hospitality industry. Therefore, the main purpose of this study is to analyse the dimensionality of the concept of perceived value in P2P accommodation, adapting the PERVAL scale of measurement. Five dimensions will be studied which inclusive of functional value, value for money, emotional value, social value and novelty value. These dimensions will be tested on how it may contribute to the overall perceived value in P2P accommodation. The proposed study which is quantitative in nature attempt to collect primary data via web based questionnaire. Data will be analysed using SPSS version 22.0. The results will be used to develop potential marketing strategies for the P2P accommodation industry consequently. Management implications and academic contributions of the research are discussed.